High Rate of Virological Response to Peginterferon α-2a–Ribavirin Among Non-Cirrhotic Iranian Hemophilia Patients With Chronic Hepatitis C - Alavi Moghaddam, Mostafa (Kowsar, 2012)
BACKGROUND: Hepatitis C is a major reason of morbidity and mortality among hemophilia patients. Although combination therapy with peginterferon (peg-INF) and ribavirin is considered as standard treatment for chronic hepatitis C (CHC), but more evidence of the efficacy and safety is needed. OBJECTIVES: In this study, efficacy and tolerability of combination therapy with peginterferon α-2a–ribavirin was investigated among hemophilia HCV infected patients. PATIENTS AND MATERIALS: In a quasi-experimental, 45 naive hemophilia patients with chronic HCV received 180 mg of pegylated interferon (Pegasys) by subcutaneous injection weekly plus an oral dose of 800-1200 µg ribavirin daily according to body weight. The treatment continued 48 weeks in patients with genotype one and 24 weeks in those with genotype 3. Sustained virological response (SVR) was considered as efficacy of treatment. RESULT: Forty three patients (95.6%) reached to end of treatment response (ETR); only two (4.4%) patients did not respond and were discontinued from treatment. None of 43 patients relapsed. SVR obtained in 43 of 45 patients (95.6%), in multivariate logistic regression model, third month’s treatment WBC (WBC > 2000) remained the only significant predictor of SVR. Regimen dose reduced in three patients; two of those because of ALT increasing and other one for his retinal bleeding. In repeated measurement analysis, alanine aminotransferase (ALT) and hemoglobin (Hb) decreased significantly during treatment, but reduction of platelet (PLT) was not significant. CONCLUSONS: Results show high efficacy and safety of combination therapy of Peg-IFN-α 2a plus ribavirin among hemophiliacs with chronic hepatitis C.